2013
DOI: 10.1016/j.bpj.2013.05.061
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Molecule Kinetics Reveal Cation-Promoted DNA Duplex Formation Through Ordering of Single-Stranded Helices

Abstract: In this work, the kinetics of short, fully complementary oligonucleotides are investigated at the single-molecule level. Constructs 6-9 bp in length exhibit single exponential kinetics over 2 orders of magnitude time for both forward (kon, association) and reverse (koff, dissociation) processes. Bimolecular rate constants for association are weakly sensitive to the number of basepairs in the duplex, with a 2.5-fold increase between 9 bp (k'on = 2.1(1) × 10(6) M(-1) s(-1)) and 6 bp (k'on = 5.0(1) × 10(6) M(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
143
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(168 citation statements)
references
References 66 publications
(87 reference statements)
24
143
1
Order By: Relevance
“…A relatively linear target concentration dependence is observed, as expected from the diffusion-limited process. At a target concentration of 100 nM, however, k hyb does not appreciably increase because under these conditions, k hyb is reaction-limited, an observation consistent with ensemble3132 and single-molecule fluorescence resonance energy transfer studies2. In addition, k hyb at the 1 and 10 nM concentrations are expected to be accelerated compared to the 100 nM concentration, since the contribution of intermediate pathways to k hyb becomes insignificant at these lower concentrations, again consistent with ensemble studies133334.…”
Section: Resultssupporting
confidence: 73%
“…A relatively linear target concentration dependence is observed, as expected from the diffusion-limited process. At a target concentration of 100 nM, however, k hyb does not appreciably increase because under these conditions, k hyb is reaction-limited, an observation consistent with ensemble3132 and single-molecule fluorescence resonance energy transfer studies2. In addition, k hyb at the 1 and 10 nM concentrations are expected to be accelerated compared to the 100 nM concentration, since the contribution of intermediate pathways to k hyb becomes insignificant at these lower concentrations, again consistent with ensemble studies133334.…”
Section: Resultssupporting
confidence: 73%
“…Further complicating the analysis of nucleic acid–ion behaviors and energetics is the presence of large ensembles of conformations of the nucleic acids of interest. Thus, in addition to determining the nucleic acid–ion energetics of one nucleic acid conformation, any modeling effort must repeat this calculation many times, for each of the nucleic acid conformations that represent the overall ensemble of conformers present (3943). …”
Section: The Basicsmentioning
confidence: 99%
“…1b,c). Because the kinetics of exchange for probes of ~6–12 nt are highly sensitive to the number of complementary bases between the probe and target 7,10,11 , varying the length of the probe allows fine-tuning of the kinetic behavior to improve specificity of detection. For the probes used in this study, kinetics of binding and dissociation were found to be more closely correlated to probe length than to the melting temperature of the duplex (Supplementary Fig.…”
mentioning
confidence: 99%
“…Because the lifetime of a short DNA duplex increases as an approximately exponential function of the number of base pairs 7,10,11 , we reasoned that SiMREPS might be used to achieve excellent single-base discrimination. To test this hypothesis, we used a single fluorescent probe to discriminate between two let-7 family members, hsa-let-7a and hsa-let-7c .…”
mentioning
confidence: 99%